Comparison of Doppler waveform and mean velocity of hepatic vein in cirrhotic patients with healthy subjects and their correlation with severity of cirrhosis (Community Based Medical Journal, 2014)
This descriptive study was carried out in the Department of Radiology and Imaging, BIRDEM (Bangladesh Institute of Research and Rehabilitation in Diabetes, Endocrine and Metabolic Disorder) Dhaka during the period of 1st June 2008 to 30th May 2009, to compare the pattern of the Doppler waveform and mean velocity of hepatic vein between healthy subjects and that in cirrhotic patients and to detect possible differences and also to assess the accuracy of the detection of changes in hepatic vein waveform and mean velocity for the diagnosis of liver cirrhosis. A total of 40 cirrhotic patients and 40 healthy subjects were enrolled in this study. Doppler waveform was done in all the patients and the healthy subjects. The mean hepatic vein velocity (MHVV) was 12.22±4.22 cm/sec and 5.17±1.19 cm/sec in case and healthy group respectively. The mean MHVV difference was significantly (p